Rapporter - Michelsen, Morten; Holst, Finn; Izard Høyer, Ole; Jovanovic, Zlatko; Jul Kirkegaard-Larsen, Thomas; Korsgaard, Mathias; Ringsager, Kristine; Wierød, Lea; Holme Hansen, Thomas; Hesselager, Jens; et al. (Danish Yearbook of Musicology, 2016)
Research Projects RAMUND: A Century of Music and Radio in Denmark. Music genres, radio genres and mediatisation (Morten Michelsen) Ph.D. Projects Professional Music Teacher Practice (Finn Holst) Living a Jazz Life: constructions of identity and genre in face-to-face interviews with Danish jazz musicians of the 1950s (Ole Izard Høyer) ‘All Yugoslavia Is Dancing Rock and Roll’: Yugoslavness and the sense of community in the 1980s Yu-rock (Zlatko Jovanovic) Analytical Paradigms in Western Music Theory (Thomas Jul Kirkegaard-Larsen) Music Video Today: audiovisual remediation in post-millennial music video (Mathias Korsgaard) Rap, Rights, Respect. A musical anthropology of citizenship, cosmopolitanism and brown rappers in Denmark (Kristine Ringsager) Function of Form – Melopoetic method in song analysis with special regard to church hymns with texts by N.F.S. Grundtvig (Lea Wierød) Conferences Medieval and Renaissance Music Conference, Certaldo, July 2013 (Thomas Holme Hansen) Nineteenth-Century Grand Opera outside Paris, Copenhagen, December 2014 (Jens Hesselager) Second Congress of the Russian Society for Theory of Music (Общества теории музыки), Moscow, September 2015 (Thomas Jul Kirkegaard-Larsen) Seventeenth Nordic Musicological Congress, Aalborg, August 2015 (Mikkel Vad) Danish Musicological Society, 2012/2013-2015/2016 (Peder Kaj Pedersen)